Síntesis de Aminoácidos Marcados. I. Síntesis de DL-Valina-1-C14 y DL-Leucima-1-C14 - Bühler, Mauricio F.; Castrillón, Jose P. A.; Mitta, Aldo, Emiliano Antonio; López, Rodolfo (Comisión Nacional de Energía Atómica; Argentina, 1960)
Fil: Bühler, Mauricio F. Comisión Nacional de Energía Atómica; Argentina